(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
The study was carried out in three agricultural zones notably Owerri, Okigwe and Orlu to evaluate the economics of poultry manure use as fertilizer in Imo State, Nigeria. A total of 240 respondents were randomly selected and interviewed from twelve local government areas drawn from the three zones. Data collected were on socio-economic characteristics, stock size and manure generation, poultry manure and environmental pollution and economic consideration of recycling poultry droppings. Structured questionnaires were used for data collection. Analytical tools used were descriptive statistics such as mean, frequency distribution and percentages. The result of the survey revealed that the dominant players in the poultry industry are those between the ages of 41-50 years implying that in future, there will be decline in productivity since youths are not actively participating in the business. The survey observed that 78.33% of poultry farmers in the state stores poultry manure within the farm premises which directly contributes to environmental pollution. Result also shows that 70.83% of poultry farmers recycle poultry manure into vegetable production while those with larger output sell the excess to crop farmers. The economic benefit of recycling poultry manure by farmers for economic prosperity is high (90.83%) and this is traced from its role in conservation agriculture and soil enrichment. The study therefore recommends the use of poultry manure by all farmers as Nigeria can conserve its foreign exchange by reducing its fertilizer importation up to 50%.